Causal relationship between stock market index and exchange rate: Evidence from Nigeria - Abdulrasheed Zubair (CBN Journal of Applied Statistics, 2013)
This paper uses Johansen's cointegration to test for the possibility of co-integration and Granger-causality to estimate the causal relationship between stock market index and monetary indicators (exchange rate and M2) before and during the global financial crisis for Nigeria, using monthly data for the period 2001-2011. Results suggest absence of long-run relationship before and during the crisis. The Granger-causality tests show a uni-directional causality running from M2 to ASI before the crisis while during the period of the crisis there is absence of causality between the variables. This suggests that ASI show responsiveness to M2. Thus, absence of the direct linkage between ASI and Exchange rate shows that the market is inefficient and perhaps not derived or guided by the fundamentals.
Keywords: N20; N27; 330; Stock market index; Exchange Rate; M2; Causality; Integration; Global Economic Crisis; Nigeria